Nilai-Nilai Pendidikan Hindu Dalam Yajña Sesa di Kecamatan Basarang Kabupaten Kapuas - Riyade, Wayan Oka; Karya, I Wayan; Sigai, Ervantia Restulita L (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2023)
Yajña Sesa is the simplest food offering consisting of rice, side dishes (cooked) as symbol of gratitude to Ida Sang Hyang Widhi Wasa/God Almighty. In fact, there is a lack understanding of some people related to the form of implementation, functions and values ​​of Yajña Sesa. The theories used in this study are the theory of symbols, structural functional theory and value theory. The research method used is a qualitative method. The types of data sources are primary and secondary data sources. This study used purposive sampling and data collection techniques with observation, interviews and document study.